Role of NADPH oxidase pathway in renal protection induced by procyanidin B2: In L-NAME induced rat hypertension model. (August 2018) - Ding, Hong; Li, Xiaofei; Li, Jian; Li, Zhike; Niu, Yunhui; Ren, Wanying; Tan, Jianyang; Yin, Shanye
Highlights: Procyanidin B2 reduced elevated blood pressure and improved renal function in hypertensive rat. Procyanidin B2 positively altered the change in renal pathophysiological markers. Procyanidin B2 reversed the increased levels on renal apoptosis and abnormal oxidative stress. AT1R and NADPH oxidase were involved the renal protective effect of procyanidin B2. Abstract: The present study examined the effects of procyanidin B2 (PB2) on L-NAME (nitric oxide synthase inhibitor)-induced hypertensive nephropathy. After 4 weeks of treatment with daily PB2 supplementation, lower blood pressure levels were observed in rats. The potential mechanisms were combined with amelioration of renal function impairment. The L-NAME–induced renal histological damage were reduced by PB2 treatment, which showed similar protective tendency in kidney injury molecule–1, nephrin, fibronectin and α–smooth muscle actin protein expression. This appears to be due to PB2 inducing a less pronounced generation of renal reactive oxygen species and inflammatory mediators than in the model group. Downregulation of Ang II type 1 receptor and NADPH oxidase subunit (NOX4, gp91phox and p47phox) played a critical role in the effect of PB2 reducing oxidative stress production. These activities could further support the use of PB2 commercially in food for the prevention of hypertension and its complications.